TICSA approach: five important aspects of multi-agent systems - Hadzic, Maja; Chang, Elizabeth (Springer, 2008)
The issues of distributed and heterogeneous information, lack an underlying knowledge base, autonomy of the information resources, dynamic nature of the information retrieval process and dramatically increase of the available information are major factors hindering efficient and effective use of the available information. In this paper we explain the importance of multi-agent systems in addressing these issues effectively and illustrate this on an example of multi-agent system designed to intelligently retrieve human disease information. We also present a conceptual framework (TICSA) which focuses on the five different aspects of multi-agent systems namely, agent Types, Intelligence, Collaboration, Security and Assembly. This framework can be used to provide insight and guidance during the multi-agents systems design.